Non-pharmacological Treatment Challenges in Early Parkinson's Disease for Axial and Cognitive Symptoms: A Mini Review - Sharpe, Gabriella; Macerollo, Antonella; Fabbri, Margherita; Tripoliti, Elina (Frontiers in Neurology, 2020)
Background: Parkinson’s disease (PD) is now known to be a multisystemic heterogeneous neurodegenerative disease, including a wide spectrum of both motor and nonmotor symptoms . PD patients’ management must encompass a multidisciplinary approach to effectively address its complex nature. There are still challenges in terms of treating axial (gait, balance, posture, speech and swallowing) and cognitive symptoms that typically arise with disease progression, becoming poorly responsive to dopaminergic or surgical treatments. Objective: to further establish the presentation of axial and cognitive symptoms, in early PD (Hoehn and Yahr scale ≤ 2) and to discuss the evidence for non-pharmacological approaches in early PD. Results: mild and subtle changes in the investigated domains can be present even in early PD. Over the last 15 years few randomized clinical trials have been focused on these areas. Due to the low number of studies and the heterogeneity of the results no definitive recommendations are possible. However, positive results have been obtained, with effective treatments being high intensity treadmill and cueing for gait disturbances, high intensity voice treatment, Video Assisted Swallowing Therapy for dysphagia and Warm-up exercises and Wii FitTM training for cognition. Conclusions: Considering the association of motor, speech and cognitive function, future trials should focus on multidisciplinary approaches to combined non-pharmacological management. We highlights the need to a more unified approach to managing these “orphan” symptoms, from the very beginning of the disease. The concept “the sooner the better” should be applied to multidisciplinary non-pharmacological management in PD.